A promise not fulfilled: The (non) implementation of the resilience turn in EU peacebuilding. Issue 2 (2nd April 2020) - Joseph, Jonathan; Juncos, Ana E.
ABSTRACT: The article provides a critical overview of the rise of resilience at the European Union (EU) level and to what extent its adoption is reshaping the terms of the EU's peacebuilding interventions. It argues that resilience offers a four-fold contribution to promoting sustainable peace: (1) a focus on complexity; (2) a systems approach; (3) a shift toward local capacities; and (4) an emphasis on human agency. The article then applies this framework to assess the implementation of the EU's "resilience turn" since the adoption of the EU Global Strategy in 2016. Focusing on the EU's discourse and its peacebuilding practices in the Western Balkans, the evidence suggests that the EU has only embraced a systems/integrated approach, while neglecting deeper understandings of complexity, local capacities and human agency. As a result, the contribution of resilience to EU peacebuilding remains limited.